Finishing lambs using an integral feed under a restricted-feeding program in an intensive production system in Northern Mexico - Rodríguez-Hernández, Karla; Maldonado-Jáquez, Jorge A.; Granados-Rivera, Lorenzo D.; Sánchez-Duarte, Juan I.; Domínguez-Martínez, Pablo A.; Torres-Hernández, Glafiro; Argüelles-Verdugo, Emanuel A. (Austral Journal of Veterinary Sciences, 2019)
The objective of this study was to compare the productive performance of finishing lambs using an integral diet under a restricted-feeding program. Ten Dorper lambs were assigned to two homogenous groups according to live weight and age under a complete randomised block design. Group 1 was fed a traditional diet commonly used by the producer and group 2 was fed an integral feed restricted to 75% of dry matter requirement of lambs. The evaluated variables were: dry matter intake, initial and final live weight, daily weight gain, feed efficiency and body growth expressed in height, body length, thoracic diameter, cane length and cane width. A partial cost analysis was carried out to evaluate the economic viability. Lambs fed with the integral feed had better feed efficiency, higher dry matter intake, daily weight gain, height, body length and thoracic diameter when compared with the lambs fed the traditional diet. The use of an integral feed under a restricted-feeding program reduced the cost of finishing lambs by 2.46 dollars per head and finishing length by 120 days. Overall, providing an integral feed under a restricted-feeding program is a viable alternative for improving finishing lambs under intensive conditions in the Northern Mexico.